A lysosome-targeted BODIPY as potential NIR photosensitizer for photodynamic therapy. (December 2017) - Li, Mingle; Tian, Ruisong; Fan, Jiangli; Du, Jianjun; Long, Saran; Peng, Xiaojun
Abstract: As an indispensable organelle, lysosomes play critical role in cell digestion and are closely relate to cell death and apoptosis. Photosensitizers that target to lysosomes are extremely important to photodynamic therapy. Herein, we report an excellent BODIPY based photosensitizerMBDP for lysosome targeting NIR photosensitizer.MBDP exhibits excellent PDT efficiency with low IC50 of 0.2 μM compared to the classical photosensitizer Ce6 (IC50  = 1.39 μM). Furthermore, MBDP can localize in lysosomes of cancer cells and produce significant singlet oxygen with photoexcitation of 660 nm red light. Additionally, lysosome destruction test and photoinduce cell death assay demonstrate thatMBDP -mediated PDT is able to damage the lysosome integrity severely and result in cell apoptosis and death in lysosomal related pathway. Graphical abstract: Highlights: A lysosomes targeted BODIPY photosensitizer, MBDP, is synthesized. MBDP exhibits excellent PDT efficiency compared to classical photosensitizer Ce6. MBDP -mediated 1 O2 generation can disrupt lysosomes of cancer cells. MBDP -mediated PDT can induce cell apoptosis and death in lysosomal related pathway.